Un tasso racconta: tra cambiamenti culturali e cambiamenti climatici - Ghelardini, Luisa; Matteucci, Daniele; Capretti, Paolo; Morelli, Emanuela (Ri-Vista. Research for landscape architecture, 2019)
A hundred-year-old yew tree (Taxus baccata L.) was felled at the Cascine Park, in Florence, Italy, providing an opportunity for both a dendrochronological study and an insight into the importance of this tree in the culture of gardens from antiquity to current times. Due to its longevity and wood durability and its growth pattern (quick response to environmental change), T. baccata is most suitable for dendrochronological analysis. This study contributed to elucidating the role of T. baccata as a bioindicator and to considering the vulnerability of monumental plants in historical gardens to climate change. These trees play the role of guardians of time in remembering us how much the comprehension of the past is essential for designing the future. Reintroducing plants in historical gardens requires careful evaluation of their symbolic and compositional functions in garden architecture without forgetting that their ecophysiological needs might remain unmet under changed climatic conditions.